KUAT TEKAN BETON CAMPURAN GGBFS DAN FLY ASH MENGGUNAKAN RETARDER - Anni Susilowati; Iqbal Yusra (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2021)
Abstract One of the world's construction needs is casting in large volumes that require concrete with low hydration heat, and one of the problems is that the concrete has a setting during the casting queue. Therefore, a research was conducted on adding retarder to concrete with a mixture of GGBFS and Fly Ash. The purpose of this research was to analyze the physical and mechanical properties of concrete, the effect of adding retarder and obtain optimal retarder levels. This research used an experimental methods to make concrete specimens of 75% cement mix: GGBFS 15%: Fly Ash 10% with a water cement ratio of 0.5 using mix design SNI-03-2834-2000. Variations of the retarder added to the concrete mixture were 0%, 0.2%, 0.4%, and 0.6% by weight of cement with the Naptha RD 31 type. Analysis of the effect of the retarder used statistical regression test methods on SPSS. The results of research obtained the longest setting time in this researchwas 1890 minutes at a variation of 0.6% with a slump of 168 mm. The compressive strength of the concrete increased by 12.07% - 52.36% by using a retarder added material. Based on the research results, it was obtained that the optimum level of use of retarder in mixed concrete GGBFS and Fly Ash was 0.2% because it has the best physical and mechanical properties. Keywords: Fly Ash, GGBFS, Compressive Strength, Retarder